2016
DOI: 10.1021/acssuschemeng.6b01411
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Continuous Conversion of Fructose to 2,5-Dihydroxymethylfuran and 2,5-Dimethylfuran

Abstract: Selective conversion of fructose to fuels and fine chemicals is an important step for biomass utilization. In this paper, direct conversion of fructose to 2,5-dihydroxymethylfuran and 2,5dimethylfuran was first realized over combined HY zeolite and inexpensive hydrotalcite (HT)-Cu/ ZnO/Al 2 O 3 in a fixed-bed reactor. The cooperative effect of HY zeolite and γ-butyrolactone solvent facilitated the dehydration of fructose into 5-hydroxymethylfurfural. By adjusting the hydrogenation temperature for HMF over HT-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 25 publications
(50 reference statements)
3
49
0
Order By: Relevance
“…[33] Hansen et al reported the catalytic conversion of HMF over aC udoped porousm etal oxide in supercritical methanol,a nd ac ombined yield [DMFa nd 2,5-dimethyltetrahydrofuran (DMTHF)]o f5 8% was achieved. [43] Wang and co-workerss tudied the CTH/hydrogenolysis of HMF to DMF over NiÀCo/C with formic acid as hydrogen donor with the highestD MF yield of 90.0 %. [35,36] Fu and coworkers used Ni-tungsten carbide and perovskite-type oxide supported Ni catalysts for the conversion of HMF into DMF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] Hansen et al reported the catalytic conversion of HMF over aC udoped porousm etal oxide in supercritical methanol,a nd ac ombined yield [DMFa nd 2,5-dimethyltetrahydrofuran (DMTHF)]o f5 8% was achieved. [43] Wang and co-workerss tudied the CTH/hydrogenolysis of HMF to DMF over NiÀCo/C with formic acid as hydrogen donor with the highestD MF yield of 90.0 %. [35,36] Fu and coworkers used Ni-tungsten carbide and perovskite-type oxide supported Ni catalysts for the conversion of HMF into DMF.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42] They also studied the one-step continuous conversiono ff ructoset o DMF over combined HY zeolite and HT-Cu/ZnO/Al 2 O 3 in af ixed-bed reactor with aD MF yield of 40.6 %. [43] Wang and co-workerss tudied the CTH/hydrogenolysis of HMF to DMF over NiÀCo/C with formic acid as hydrogen donor with the highestD MF yield of 90.0 %. [44] Yuan and co-workersr ecently reportedt hat CuÀCo bimetallic nanoparticles coated with carbon layers were very efficient catalysts for the HDO of HMF to DMF.…”
Section: Introductionmentioning
confidence: 99%
“…This was tested in a continuous flow setup where HY zeolite was loaded to act as catalyst. It was observed that the dehydration reaction was promoted at 140 • C, while hydrogenation performed better at 240 • C, obtaining yields of 2,5-DHMF of 48.2% and 2,5-DMF of 40.6% [54].…”
Section: Transformations Of Fructose Through 5-hmf Related Routesmentioning
confidence: 99%
“…In general, transformation of carbohydrate to DMF is a two‐step process. In the first step, dehydration of carbohydrates to 5 HMF using Lewis or Brønsted acid catalyst was achieved and in second step, the hydrogenolysis of HMF to DMF was obtained using a metal catalyst , . Roman‐Leshkov et al .…”
Section: Introductionmentioning
confidence: 99%
“…reported 40% DMF yield from fructose in continuous fixed bed reactors at 240 °C. Two fixed bed reactor were used, HY zeolite catalyst packed in first fixed reactor and Cu/ ZnO/Al 2 O 3 catalyst packed in second fixed bed reactor . Wei et al .…”
Section: Introductionmentioning
confidence: 99%